Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/biom13030471
|View full text |Cite
|
Sign up to set email alerts
|

The Lysophospholipase PNPLA7 Controls Hepatic Choline and Methionine Metabolism

Abstract: The in vivo roles of lysophospholipase, which cleaves a fatty acyl ester of lysophospholipid, remained unclear. Recently, we have unraveled a previously unrecognized physiological role of the lysophospholipase PNPLA7, a member of the Ca2+-independent phospholipase A2 (iPLA2) family, as a key regulator of the production of glycerophosphocholine (GPC), a precursor of endogenous choline, whose methyl groups are preferentially fluxed into the methionine cycle in the liver. PNPLA7 deficiency in mice markedly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Given that the kidney is a site of disseminated candidiasis ( 45 ), it is noteworthy that GPC is also a renal osmolyte reported to be present in renal cells at roughly 18 nmoles/mg protein ( 46 , 47 , 48 , 49 ). The GPC content in other host microenvironments is unknown and likely dynamic, because GPC is liberated through phospholipase-mediated PC hydrolysis ( 50 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the kidney is a site of disseminated candidiasis ( 45 ), it is noteworthy that GPC is also a renal osmolyte reported to be present in renal cells at roughly 18 nmoles/mg protein ( 46 , 47 , 48 , 49 ). The GPC content in other host microenvironments is unknown and likely dynamic, because GPC is liberated through phospholipase-mediated PC hydrolysis ( 50 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although quantitative metabolomic data on GPC are limited, it is clear that serum P i (at roughly 1 mM [ 26 , 27 ]) is more abundant than serum GPC ( 19 , 25 ). However, the relative concentrations of GPC and P i in host microenvironments have not been established and are undoubtedly dynamic, as GPC is liberated through phospholipase-mediated PC hydrolysis, during which it may reach higher concentrations than those found in serum at a steady state, while serum and cytosolic P i concentrations are highly regulated ( 17 , 46 , 47 ). Both phospholipase B1 and B5 are required for full virulence of C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…The patatin-like phospholipase domain containing protein no. 7 (PNPLA7) is another candidate mammalian enzyme that possesses a general lysophospholipase activity. In mammals, PNPLA7 is a 150 kDa (∼1300 amino acids) ER-resident integral membrane enzyme from the mSH family that shows expression and activity only in the metabolic active tissues (primarily liver and kidneys, and to a lesser extent in the lungs) (UniProt ID: Q6ZV29 for human PNPLA7). ,, Recent in vitro biochemical studies have shown that PNPLA7 has robust lysophospholipase activity against several lysophospholipid substrates, including lyso-PS . Overexpression of PNPLA7 activity in mammalian COS-7 cells results in decreased production of several lysophospholipids, including lyso-PS .…”
Section: Enzymes Metabolizing Lyso-pss In Mammalian Cells and Tissuesmentioning
confidence: 99%